Metabolomic and sensomic approach to characterize key aroma of aromatic mangoes from Indonesia - MARIA BELGIS; YULI WITONO; GIYARTO GIYARTO; NUR FATHONAH SADEK; ELOK LUTFI MASRUROH; HERLINA HERLINA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Belgis M, Witono Y, Giyarto, Sadek NF, Masruroh EL, Herlina. 2023. Metabolomic and sensomic approach to characterize key aroma of aromatic mangoes from Indonesia. Biodiversitas 24: 2242-2250. Garifta Merah, Garifta Orange, and Agri Gardina 45 are new mango cultivars with a strong aroma and attractive color from Indonesia. This study investigated aromatic constituents and sensory profiles using a combination of metabolomic and sensomic approaches of Garifta Merah, garifta Orange, and Gardina 45. Volatile compounds were extracted using Head Space-Solid Phase Microextraction (HS-SPME), then identified using Gas Chromatography-Mass Spectrometry (GC-MS). Sensory descriptive Rate All That Apply (RATA) and hedonic tests were used for sensory attributes profiling and aroma-liking evaluation. Monoterpene hydrocarbons were the predominant volatile compound in all cultivars; however, it was also accompanied by esters in Garifta Orange and Agri Gardina 45. The Principal Component Analysis (PCA) classified those cultivars into different groups. Garifta Merah was characterized by higher ?-pinene, while Garifta Orange was characterized by high ethyl butanoate. Agri Gardina was in the separate group characterized by ?-trans ocimene, ethyl butanoate, and isopentyl butanoate. The identified compounds in all cultivars had Odor Active Value (OAV)>1 and correlated to their sensory profile described by assessors. Garifta Orange was perceived to have the highest overall aroma liking among all cultivars. It was presumably due to the high ethyl butanoate content related to the pineapple, mango, fruity, and fermented attributes.